Analisis Uang Wariq Dalam Sosiologi Ilmu Pengetahuan - Muhammad Alfan Rumasukun (Islamic Economics Journal, 2019)
The current facts have shown that the sharia economic growth trend in Indonesia continues to increase, both on a macro and micro scale. That can happen through massive programs of education and sharia economic exhibitions in the midst of the academic community and the general public, as well as increasingly raising awareness of Muslims about the application of sharia in the economic field. The progress of Islamic finance seems to be inseparable from the use of exchange instruments, namely money made from gold and silver or commonly referred to as Dinar and Dirham money. It is in this context that some sharia economists have revived the use of dinars and dirhams as an alternative solution to the problem of modern banknotes. On the same occasion, in some literature, classical fiqh was allegedly a history of wariq money that had existed in Islam even long before the presence of Islam was seen by the Prophet. Wariq money was explicitly approved in the story of the faithful youth of the cave dwellers which were published in the Qur’an Surat al-Kahf verse 19. This study aims to: (1) get a complete picture of the concept of wariq money, and (2) to reveal the relevance of wariq money to sharia economics.The type of research used in this study is literature research with historical studies and reading texts from various classical and contemporary fiqh. In this context, the reference sources offered are a number of fiqh books from among the four fiqh schools which have been selected from the library collection of the Universitas Darussalam Gontor Primary School. To get complete data is done by the screening process and analysis of wariq terms from some of the fiqh books. Screening and analysis is done by collecting various primary references related to the discussion of the wariq, so as to enable a complete description of the term money wariq. This data is then processed and analyzed with the sociological theory of science to be approved by the validity of the overall money concept. The conclusions obtained from this study, wariq money is money made from silver in the form of sheets of paper that have been around since the time of kahfi ashabul. Second, wariq money is very relevant to be used as an alternative solution for the consideration of finance and state finances.